The Pathology of Pathogenic Theileriosis in African Wild Artiodactyls. Issue 1 (January 2020) - Clift, Sarah J.; Collins, Nicola E.; Oosthuizen, Marinda C.; Steyl, Johan C. A.; Lawrence, John A.; Mitchell, Emily P.
The published literature on schizont-"transforming, " or pathogenic theileriosis, in African wild artiodactyls is dated and based on limited information. Here the authors review the taxonomy, diagnosis, epidemiology, hematology, pathology, and aspects of control in various species. Molecular studies based on 18S and 16S rRNA gene sequences have shown that African wild artiodactyls are commonly infected with diverse Theileria spp., as well as nontheilerial hemoprotozoa and rickettsia-like bacteria, and coinfections with pathogenic and nonpathogenic Theileria species are often recorded. Although theileriosis is still confusingly referred to as cytauxzoonosis in many species, the validity of a separate Cytauxzoon genus in artiodactyls is debated. The epidemiology of theileriosis is complex; the likelihood of fatal disease depends on the interplay of parasite, vertebrate host, tick vector, and environmental factors. Roan calves ( Hippotragus equinus ) and stressed animals of all host species are more susceptible to fatal theileriosis. Even though regenerative anemia is common, peripheral blood piroplasm parasitemia does not correlate with disease severity. Other than anemia, common macroscopic lesions include icterus, hemorrhages (mucosal, serosal, and tissue), fluid effusions into body cavities, lung edema, and variably sized raised cream-colored foci of leukocyte infiltration in multiple organs. Histopathologic findings include vasocentric hyperproliferation and lysis of atypical leukocytes with associated intracellular schizonts, parenchymal necrosis, hemorrhage, thromboembolism, and edema. Immunophenotyping is required to establish the identity of the schizont-transformed leukocytes in wild ungulates. Throughout the review, we propose avenues for future research by comparing existing knowledge on selected aspects of theileriosis in domestic livestock with that in African wild artiodactyls.